(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Hemodynamic stability during surgical anaesthesia in various surgeries have become a great concern. During operative procedure, patient with or without preexisting hypertension are at risk of development of peroperative hemodynamic instability. Surgical stress response induced by anxiety, surgical stimulation, pain can adversely affect the peroperative hemodynamic parameters, particularly in hypertensive patients. Objectives: To assess the role of lorazepam premedication on hemodynamic stability during peroperative period in patients with hypertension undergoing upper abdominal surgery. Materials & Methods: This was a prospective, observational study, carried among 46 hypertensive patients controlled by single anti-hypertensive drug who were scheduled for different upper abdominal surgeries at Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2017 to June 2017. Patients were divided into two groups of twenty three patients each where Group I-received placebo tablet and Group II received lorazepam (1 mg). Hemodynamic parameters heart rate, systolic and diastolic blood pressure, ECG and peripheral capillary oxygen saturation (SpO2) were recorded just after intubation and 10 minutes interval during operative procedure. Results: Among 23 patients of Group I, mean age was 41.78 ± 7.6 years and duration of surgery was 85.09± 19.91 minutes, while in Gropu II mean age was 42.02 ± 6.7 years and duration of surgery was 84.35 ± 17.04 minutes. Baseline values of heart rate, systolic blood pressure and diastolic blood pressure of two groups were not statistically significant. All these parameters were changed in both groups immediately after intubation and 10, 20, 30, 40, 50 and 60 minutes of peroperative period. And these difference of changes of hemodynamic parameters of two groups were found statistically significant. Regarding ECG tracing and peripheral capillary oxygen saturation (SpO2), no significant changes was found in either group. Conclusion: Lorazepam significantly attenuetes hemodynamic changes in controlled hypertensive patients undegoing upper abdominal surgery. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 30-34